Role of Small Molecule Targeted Compounds in Cancer: Progress, Opportunities, and Challenges - Sun, Guoqiang; Rong, Dawei; Li, Zhouxiao; Sun, Guangshun; Wu, Fan; Li, Xiao; Cao, Hongyong; Cheng, Ye; Tang, Weiwei; Sun, Yangbai (Frontiers in Cell and Developmental Biology, 2021)
Research on molecular targeted therapy of tumors is booming, and novel targeted therapy drugs are constantly emerging. Small molecule targeted compounds, novel targeted therapy drugs, can be administered orally as tablets and others, which do not draw upon genes, causing no immune response. It is easy to be structurally modified to make it more applicable to clinical needs, and convenient to promote since low cost. It refers to a hotspot in the research of tumor molecular targeted therapy. In the present study, we review the current Food and Drug Administration(FDA)-approved use of small molecule targeted compounds in tumors, summarize the clinical drug resistance problems and mechanisms facing the use of small molecule targeted compounds, and predict the future direction of the evolving field.